Eugen Biser: una aproximación a su persona y obra - Sörgel, Rainer (Estudios eclesiásticos, 2013)
Eugen Biser, German theologian and successor to Karl Rahner in the Romano Guardini Chair in Munich, is relatively unknown in comparison with previous occupants of the Guardini Chair. His theological work is extensive, complex, and his thought original. This study offers an approach to his person and theological work. It summarizes the most important periods of his life and lays out the principal lines of his theological thought. The presentation concludes with a select bibliography that will offer the reader interested in Biser an opportunity to delve more deeply.